A qualitative analysis of cancer patients’ perceptions of an interprofessional counseling service on complementary and integrative healthcare - Dürsch, Helena; Boltenhagen, Ursula; Mahler, Cornelia; Joos, Stefanie; Szecsenyi, Joachim; Klafke, Nadja (Qualitative health research, 2024)
Medical guidelines recommend actively addressing patients’ information needs regarding complementary and integrative healthcare (CIH). Within the CCC-Integrativ study, an interprofessional counseling program on CIH was developed and implemented at four comprehensive cancer centers (CCCs) in Germany. As part of the process evaluation, this study examines cancer patients’ experiences with interprofessional CIH counseling sessions conducted by a physician and a nurse. Forty problem-centered interviews were conducted using a semi-structured interview guide. All interviews were audio-recorded, transcribed verbatim, and analyzed using deductive-inductive content analysis based on Kuckartz and Rädiker’s approach. Findings revealed that most participants had prior experience with CIH approaches and were burdened by physiological and psychological symptoms. Counseling sessions focused on cancer- and treatment-related symptoms and appropriate CIH recommendations (e.g., herbal poultice against anxieties and acupressure against nausea). Participants appreciated the mutual exchange and integration of perspectives from different healthcare professions within the interprofessional approach. They noted that the counseling team comprehensively addressed their healthcare and CIH information needs. Suggestions for improvement included the specificity of the CIH recommendations. As the participants only received counseling and no CIH treatments, information about reputable CIH providers was particularly important to many seeking advice. Patients with cancer receiving tailored CIH counseling from two healthcare professionals experienced benefits in CIH counseling for symptom management. The interprofessional teams offered a comprehensive perspective on patients’ needs, proposing personalized recommendations for symptom control. These insights may foster collaboration between healthcare professionals interested in CIH counseling, enabling them to expand and consolidate their counseling services.